PENGARUH KEPEMIMPINAN DAN KOMPETENSI TERHADAP KINERJA GURU SMK ATLANTIK - Ardhi Ashadi; Widodo Widodo (Universitas Muhammadiyah Metro Lampung, 2020)
This study is aims to examine to the effects of leadership and competence toward the teacher’s performance in SMK Atlantik. Leadership (X1) and competence (X2) are independent variables and the performance of the teacher (Y) is dependent variable. Based on the results of the study, then obtained the following conclusions: (1) found a positive and significant relationship between leadership (variable X1) to the performance of the teacher (variable Y) with the correlation result obtained a number of 70.8%, so Ho rejected and Ha accepted (2) found that the connection is positive and significant because it gets a figure of 81.4%, so Ho rejected and Ha accepted between competence (X2) on teacher performance (Y). (3) Since getting 83.3% results means collectively found which is a positive and significant relationship between the principal’s leadership variables (X1) and the motivational variables (X2) against the teacher’s performance variable (Y).Keywords: Leadership, Competence, Performance